Asian perspectives on NAPCRG. Issue 3 (19th September 2022) - Lee, Eng Sing; Kaneko, Makoto; Kusaba, Tesshu
Abstract : This is a short communication to reflect on experiences at North American Primary Care Research Group (NAPCRG) conference from the perspective of Asian family physicians. They feel that NAPCRG can play an important role to level up the skills and talents in countries with less-established primary care research capacity and capability. NAPCRG should not be restricted to networking functions for only North America, Europe and Oceania but should include Asia, South America and Africa. These international academic networks will strengthen primary care research in the world.